2020
DOI: 10.48550/arxiv.2009.10079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of Stellar Feedback in HII Regions

Grace M. Olivier,
Laura A. Lopez,
Anna L. Rosen
et al.

Abstract: Stellar feedback is needed to produce realistic giant molecular clouds (GMCs) and galaxies in simulations, but due to limited numerical resolution, feedback must be implemented using subgrid models. Observational work is an important means to test and anchor these models, but limited studies have assessed the relative dynamical role of multiple feedback modes, particularly at the earliest stages of expansion when H ii regions are still deeply embedded. In this paper, we use multiwavelength (radio, infrared, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…One possibility is that our simulation captures a tendency for massive stars to form in denser environments, either due to suppression of fragmentation (Krumholz & McKee 2008) or due to more favorable conditions for accretion (Bonnell et al 2007). If so, those stars would irradiate denser gas and produce smaller HII regions, reducing the efficiency of ionization (Olivier et al 2020). Another possibility is that our higher resolution in dense regions allowed us to resolve the upper tail of the density PDF better, and thus more accurately model the formation of clumpy, porous gas structures that would be more resilient to ionization.…”
Section: Athena Gmc Simulations With Uv Feedbackmentioning
confidence: 99%
“…One possibility is that our simulation captures a tendency for massive stars to form in denser environments, either due to suppression of fragmentation (Krumholz & McKee 2008) or due to more favorable conditions for accretion (Bonnell et al 2007). If so, those stars would irradiate denser gas and produce smaller HII regions, reducing the efficiency of ionization (Olivier et al 2020). Another possibility is that our higher resolution in dense regions allowed us to resolve the upper tail of the density PDF better, and thus more accurately model the formation of clumpy, porous gas structures that would be more resilient to ionization.…”
Section: Athena Gmc Simulations With Uv Feedbackmentioning
confidence: 99%
“…In a study of massive star clusters in the Milky Way's Central Molecular Zone, Barnes et al (2020) find that indirect radiation pressure is important at early times (< 1 Myr). Similarly, Olivier et al (2020) find that dust-reprocessed radiation pressure is the dominant feedback mechanism in ultra compact HII regions in the Milky Way. Moreover, given the possible underestimate of the stellar masses due to absorption of ionizing photons by dust or evolution beyond the ZAMS (which are not reflected in the error bars in Figure 11), indirect radiation pressure is a plausible mechanism to drive the observed outflows.…”
Section: Dust-reprocessed (Indirect) Radiation Pressurementioning
confidence: 77%
“…Since we find (see Paper II, Figure 17) that as little as 1% of the input energy remains in our simulation, we conclude that radiative cooling in turbulent mixing layers would easily account for the missing wind energy in observed star-forming regions. Olivier et al (2020) recently observed deeply embedded HII regions, where our theory should be most applicable, but were only able to put upper limits on effects of stellar winds due to a lack of long-exposure X-ray observations. Further work on this front should allow a quantitative test of our theory.…”
Section: Observationsmentioning
confidence: 96%
“…This includes observations of evolved clusters in the Large Magellanic Cloud (LMC) by Pellegrini et al (2011); Lopez et al (2011Lopez et al ( , 2014; McLeod et al (2019), in the Milky Way (Rosen et al 2014), in nearby 'normal' galaxies (McLeod et al 2020;Chevance et al 2020b), and in nearby galaxies with more extreme star-forming environments (Levy et al 2020). The recent works of Olivier et al (2020) and Barnes et al (2020) have sought to make the same evaluation but at very early times (in deeply embedded clusters) in the Milky Way.…”
Section: Introductionmentioning
confidence: 99%